Discrete inequalities based on multiple auxiliary functions and their applications to stability analysis of time-delay systems. Issue 12 (December 2015) - Nam, P.T.; Trinh, H.; Pathirana, P.N.
Abstract: This paper presents new discrete inequalities for single summation and double summation. These inequalities are based on multiple auxiliary functions and include the Jensen discrete inequality and the discrete Wirtinger-based inequality as special cases. An application of these discrete inequalities to analyze stability of linear discrete systems with an interval time-varying delay is studied and a less conservative stability condition is obtained. Three numerical examples are given to show the effectiveness of the obtained stability condition.